Jurisdictional conflict on interfaith custody dispute in Malaysia: challenges and prospect for reform - Mohamed Jani, Hidayati; Mohd Zin, Najibah (The Faculty of Law, Universiti Teknologi MARA (UiTM), 2016)
Interfaith custody dispute is one of the area in which the conflict of jurisdiction between the civil court and the Syariah court arises. The conversion to Islam by one party to a non-Muslim marriage has an impact on the legality of the marriage, and more importantly the determination as to the custodial right of a child is very much in dispute since the parties are no longer subject to the same set of laws and courts. The current practice suggests that the converted father received custody more often than the non-Muslim mothers regardless of the age of the child. In most cases this has caused dissatisfaction particularly among non-Muslim community and given rise to an issue of whether the decision has been made in the best interest of the child especially when it involves the custodial right of a child at their tender years. Thus, this paper seeks to examine the extent of the jurisdictional conflict on interfaith custody dispute in Malaysia. The research method employs in this study is mainly a textual analysis of relevant materials and cases law relating to interfaith custody dispute. The study suggests several mechanisms to resolve the conflict where the emphasis on the best interests of the child shall be paramount.